2012
DOI: 10.1007/s10517-012-1922-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Sulfated Polysaccharides from Sea Brown Algae and Toll-Like Receptors on HEK293 Eukaryotic Cells In Vitro

Abstract: We studied the interactions between sulfated polysaccharides, fucoidans from sea brown algae Laminaria japonica, Laminaria cichorioides, and Fucus evanescens, with human Toll-like receptors (TLR) expressed on membranes of cultured human embryonic kidney cells (HEK293-null, HEK293-TLR2/CD14, HEK293-hTLR4/CD14-MD2, and HEK293-hTLR5). Fucoidans interacted with TLR-2 and TLR-4, but not with TLR-5, and were nontoxic for the cell cultures. L. japonica fucoidan (1 mg/ml), L. cichorioides fucoidan (100 μg/ml and 1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…There was a large increase in the expression of wound-healing genes for the main matrix metalloproteases: at four hours, gene expression in skin treated with the Undaria pinnatifida extract was more than doubled as compared to control, showing an enhanced wound-healing signal. The stimulation of Toll-like receptors by other types of fucoidan has been demonstrated in cell culture [22]. The increased expression of extracellular matrix enzyme genes in vitro by the Undaria pinnatifida extract may be indicative of the ability of the extract to enhance the early wound-healing response, and then modulate that response.…”
Section: Time In Daysmentioning
confidence: 99%
“…There was a large increase in the expression of wound-healing genes for the main matrix metalloproteases: at four hours, gene expression in skin treated with the Undaria pinnatifida extract was more than doubled as compared to control, showing an enhanced wound-healing signal. The stimulation of Toll-like receptors by other types of fucoidan has been demonstrated in cell culture [22]. The increased expression of extracellular matrix enzyme genes in vitro by the Undaria pinnatifida extract may be indicative of the ability of the extract to enhance the early wound-healing response, and then modulate that response.…”
Section: Time In Daysmentioning
confidence: 99%
“…The composition of the various fucoidans was analysed during the Zhang et al ., study, showing no clear structural rationale for the differences in biological effect. There was no direct correlation with sulfation levels, however the uronic acid-containing fucoidans ( Macrocystis pyrifera and Ascophyllum nodosum ) were both more effective in activating dendritic cell responses and this provides a direction for future refinement of this activity Further on in this review we discuss the Toll like receptor (TLR) stimulating activity of fucoidans [ 25 ], which is a known route to effective adjuvant activity [ 26 ].…”
Section: Comparison Between Types Of Fucoidanmentioning
confidence: 99%
“…Toll like receptors (TLRs) are a class of membrane spanning receptors that are a key part of the innate immune system. Researchers demonstrated that fucoidans from Laminaria japonica , Laminaria cichorioides and Fucus evanescens activate and bind to “toll-like receptors” in human cells [ 25 ]. Fucoidans interacted with TLR-2 and TLR-4, but not with TLR-5, and were non-toxic for the cells.…”
Section: Immune Modulationmentioning
confidence: 99%
“…Another study found that L. Japonica , L. cichoriodes , and F. evanescens polysaccharides served as TLR ligands that interacted with TLR‐2 and TLR‐4 in vitro to activate NF‐κB. This, in turn, led to the expression of the defense effector mechanism of innate immunity including secretion of cytokines, chemokines, and expression of MHC class I and II molecules, which are necessary for defense against foreign invaders and activation of adaptive immune response (Makarenkova et al, ). Negishi, Mori, Mori, and Yamori () conducted a clinical trial on adult male and female volunteers supplementing their diet with 1 g/day of fucoidan from Undaria pinnatifida for 24 weeks (Negishi et al, ).…”
Section: Prebiotics Bsp and Immunomodulation: Evidence And Mechanismmentioning
confidence: 99%